514 A Data-driven Approach to Predicting 5-ALA-Induced Fluorescence and WHO Grade in Newly Diagnosed Diffuse Gliomas. (1st March 2022) - Müther, Michael; Jaber, Mohammed; Johnson, Timothy; Orringer, Daniel A.; Stummer, Walter
Abstract : INTRODUCTION: A growing body of evidence has revealed the potential utility of 5-aminolevulinic acid (5-ALA) as a surgical adjunct in select lower-grade gliomas. However, a reliable means of identifying which lower-grade gliomas will fluoresce has not been established. METHODS: We investigated a cohort of grades II and III glioma patients who received 5-ALA prior to resection at a single institution. Using a logistic regression-based model, we evaluated 14 clinical and molecular variables considered plausible determinants of fluorescence. We then distilled the most predictive features to develop a model for predicting both fluorescence and tumor grade. We also explored the relationship between intraoperative fluorescence and molecular markers. RESULTS: 179 subjects were eligible for inclusion. Our logistic regression classifier accurately predicted fluorescence with 91.9% accuracy and revealed enhancement as the singular variable in determining fluorescence. There was a direct relationship between enhancement on MRI and the likelihood of observed fluorescence. Observed fluorescence correlated with MIB-1 index but not with IDH status, 1p19q co-deletion or MGMT promoter methylation. CONCLUSION: We demonstrate a strong correlation between enhancement on preoperative MRI and the likelihood of visible fluorescence during surgery in intermediate-grade glioma patients. Our analysis provides a robust method for predicting 5-ALA-induced fluorescence in grade II and grade III glioma patients.